Comunicação e memória empresarial : os livros institucionais da Ipiranga - 1962 e 1997 - Ordoque, Christian Astigarraga (2017)
Institutional book is one of the communication products most traditionally used by companies to publicize their trajectory. Throughout them the companies elaborate a narrative that differentiate them from their competitors. In our study, we sought to analyze two institutional books: The first book is called “Petrolinho Edição Especial Comemorativa ao 25º Aniversário da Refinaria de Petróleo Ipiranga S/A”, produced in 1962. The second book of Ipiranga has the title: “Uma História de Realizações. Empresas Petróleo Ipiranga 60 anos”, produced in 1997. Our analysis will be made through the Hermeneutics Depth method of John B. Thompson and we will use as Technical Discursive Textual Analysis of Roque Moraes, trying to answer if the books present the memory or the history of the company. For that, the analysis of three contexts is necessary; The relationship between culture and organizational communication, the debate between History and Memory and the more current context of corporate social responsibility and historical responsibility. With our study, we intend to contribute to the analysis of the insitutional book, its process of elaboration and use as an communication tool for companies.